The Multiconfiguration Time Dependent Hartree-Fock Method for Cylindrical Systems - Nakib, Protik H. (Université d'Ottawa / University of Ottawa, 2013)
Many-body quantum dynamics is a challenging problem that has induced the development of many different computational techniques. One powerful technique is the multiconfiguration time-dependent Hartree-Fock (MCTDHF) method. This method allows proper consideration of electronic correlation with much less computational overhead compared to other similar methods. In this work, we present our implementation of the MCTDHF method on a non-uniform cylindrical grid. With the one-body limit of our code, we studied the controversial topic of tunneling delay, and showed that our results agree with one recent experiment while disagreeing with another. Using the fully correlated version of the code, we demonstrated the ability of MCTDHF to address correlation by calculating the ground state ionization energies of a few strongly correlated systems.
Keywords: many-body problem; quantum dynamics; strong-field phenomenon; laser-matter interaction